New turn on Pd2+-specific fluorescence probe and its use as an imaging reagent for cellular uptake in Hct116 cells - Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new coumarin-rhodamine conjugate is used as a specific probe for Pd2+ ions and this could even delineate Pd(II) from Pd(0) or Pd(IV) in aqueous buffer medium (pH similar to 7). Laser confocal microscopic studies reveal that efficient cellular internalization of this reagent helps in imaging the cellular uptake of Pd2+ as low as 0.1 ppm in Hct 116 cells. This reagent could even be used for estimation of Pd2+ in human urine samples.